DISPLASIA FIBROSA POLIOSTÓTICA: A PROPÓSITO DE UN CASO / POLYOSTOTIC FIBROUS DYSPLASIA: A REPORT OF A CASE - Gómez Ríos, Sadia Lumis; Herrera Armenteros, Anorys Regla; Vega Conejo, Viviana; Beltrán Blanes, Yeniseys; Blanco Díaz, Ana Tamara; Reyes Shuart, Yusimí (Panorama. Cuba y Salud, 2020)
La displasia fibrosa es una enfermedad benigna rara donde existe un trastorno en la maduración del mesénquima óseo, el cual es sustituido por tejido fibroso anormal, resultado de una mutación génica esporádica en el gen GNAS1 activador de la proteína Gsα. Existen una forma monostótica y otra poliostótica que cuando se asocia a trastornos endocrinos e hiperpigmentación en la piel se denomina síndrome de McCune- Albright. El objetivo del presente artículo fue demostrar la importancia del diagnóstico precoz de la Displasia Fibrosa Poliostótica para la prevención de complicaciones. Abstract Fibrous dysplasia is a rare benign disease where there is a disorder in the maturation of the bone mesenchyme, which is replaced by abnormal fibrous tissue, the result of a sporadic gene mutation in the Gsα protein activator gene GNAS1. There is a monostotic and a polyostotic form that when associated with endocrine disorders and hyperpigmentation in the skin is called McCune-Albright syndrome. With the aim of demonstrating the importance of the early diagnosis of Polyostotic Fibrous Dysplasia for the prevention of complications, a 34-year-old male patient, male, white, suffered from a slight trauma to the left arm. humerus fracture. The interrogation revealed a history of multiple fractures in the same place. The physical examination revealed pain in the area of the trauma and limitation of movements.